Mediation: Moderation mechanism between the relationship of corporate social responsibility and employees' promotive voice behavior - Khalid Rasheed Memon; Say Keat Ooi; Saima Khalid; Bilqees Ghani (International Journal of Business Science & Applied Management (IJBSAM), 2021)
The purpose of this article is to explore the impact of corporate social responsibility on employees' promotive voice behavior through the mediation-moderation mechanism within the framework of a developing country. This is an empirical study, administered through two self-reported questionnaires. Employees of 25 manufacturing units of Pakistan are the source of data collection for this research. Data analysis was performed using SEM through SMART PLS 3. The results show a positive role of CSR for the development of employees' promotive voice behavior through indirect mechanism. The employees get psychologically empowered through organizational trust developed as a result of corporate CSR activities. Further, the employees were found to be inclined more towards the activities of personal care, concern and safety (through organizational justice used as moderator) for the development and enhancement of psychological empowerment leading towards voice behavior. The findings of the study contribute to the literature on corporate social responsibility and provide practical implications. Further, the study persuades practitioners to practice new ways of conveying the feelings of care, concern and safety, which, in turn, increase employees' psychological empowerment.
Keywords: 650; corporate social responsibility; voice behavior; psychological empowerment; social exchange theory; organizational justice